Latent class analysis to characterize neonatal risk for neurodevelopmental differences. (15th July 2022) - Momany, Allison M.; Jasper, Elizabeth; Markon, Kristian E.; Nikolas, Molly A.; Ryckman, Kelli K.
Abstract : Background: Neonatal risk factors, such as preterm birth and low birth weight, have been robustly linked to neurodevelopmental deficits, yet it is still unclear why some infants born preterm and/or low birth weight experience neurodevelopmental difficulties while others do not. The current study investigated this heterogeneity in neurodevelopmental abilities by examining additional neonatal morbidities as risk factors, utilizing latent class analysis to classify neonates into groups based on similar neonatal risk factors, and including neonates from the full spectrum of gestational age. Methods: Neonates who received neonatal care at an academic public hospital during an almost 10‐year period ( n  = 19, 951) were included in the latent class analysis, and 21 neonatal indicators of health were used. Neonatal class, sex, and the interaction between neonatal class and sex were used to examine differences in neurodevelopment at 18 months of age in a typically developing population. Results: The best fitting model included five infant classes: healthy, hypoxic, critically ill, minorly ill, and complicated delivery. Scores on the parent‐rated neurodevelopmental measure differed by class such that infants in the critically ill, minorly ill, and complicated delivery classes had lower scores. There was no main effect of sex on the neurodevelopmental measure scores, but the interaction between sex and neonatal class was significant for three out of five neurodevelopmental domains. Conclusions: The current study extends the understanding of risk factors in neurodevelopment by including several neonatal medical conditions that are often overlooked and by using a person‐centered, as opposed to variable‐centered, approach. Future work should continue to examine risk factors, such as maternal health during pregnancy and medical interventions for newborns, in relation to neonatal risks and neurodevelopment by using a person‐centered approach.